Eksplorasi Etnobiologi Kerinci Untuk Meningkatkan Pemahaman Literasi Sains Mahasiswa - Efriana Jon (Journal on Education, 2024)
Kerinci is a tribe in Kerinci Regency in Jambi Province, Indonesia. The Kerinci tribe has various customs that are passed on from generation to generation. The Kerinci area has very interesting natural resources and unique cultural traditions that attract foreign tourists. However, in the current technological era, many millennials and generation Z do not know the customs of the Kerinci tribe because there is no appropriate platform to teach them. This can be seen from the low scientific literacy abilities of current students so that their ability to solve problems is difficult, especially in lectures. In fact, prospective teacher students must be able to dig deeper into their existing competency abilities. Lecturers as teaching staff must of course be able to develop their skills in how to make lessons interesting so that prospective teacher students love and understand the cultural traditions around them which are also related to the lecture material. One of the traditions of the Kerinci community is reflected in the art of dance called the rangguk dance. The rangguk dance is usually performed during large traditional events such as the Sko kenduri event. The ranggung dance has a basic movement, namely nodding and a main movement that depicts the activity of farming in the rice fields in a cooperative manner. The stages of this research are still in the initial stages, namely preliminary and planning, such as literature studies, interviews and discussions with several experts about the need for detailed ethnobiological exploration to increase students' scientific literacy. Furthermore, observations were also made of the scientific literacy activities of lecturers and students in general biology courses. In order to support the research data, a questionnaire was distributed to students to find out their responses about ethnobiology in Kerinci. From data analysis, it was found that learning that includes ethnobiology in the learning process is highly recommended by several experts as an alternative model and also an interesting learning resource for increasing students' scientific literacy.